Eco-friendly concrete using by-products as partial replacement of cement - El-Nadoury, Wegdan W. (Frontiers in Materials, 2022)
The current challenge facing the construction industry is to produce sustainable concrete at the lowest feasible cost. One obstacle to that is the demand for an excessive amount of cement. The reduction of cement content can be achieved by its partial replacement with by-product materials that attain an appropriate pozzolanic index. Two by-products namely; Ceramic waste powder (CWP) and rice husk ash (RHA) are remarkably formed throughout tiles and rice production. Using these by-products as a partial substitution for cement reduces landfills, the cost of concrete, and climate change due to cement production. This paper investigates the effect of replacing 5%, 15%, 20%, 25%, and 30% of cement with CWP. Varied proportions of RHA; 5%, 10%, 15%, and 25% were added to the mix with the optimum CWP. The concrete mixture was proportioned to produce M35-grade concrete. Properties of concrete were assessed concerning workability, compressive, splitting tensile, and flexural strength. The results are compared to conventional concrete with 0% replacement. Results identified that 20% substitution of cement by CWP is the optimum percentage. It increases the compressive, splitting tensile, and flexural strength by 11%, 20%, and 12.5% respectively. Increasing the percentage up to 30% has minor effect on tensile and flexural strength but has destructive effect on compressive strength. Blending cement with CWP and RHA additionally improves the mechanical properties. The combination of 20% CWP/10% RHA propose superior strength, it increases the compressive, tensile, and flexural strength by 14%, 28%, and 19% compared to the control concrete.